OC-010 Endoscopic Resection Of Duodenal Adenomas – Comparison Of Safety And Efficacy Between Sporadic Adenomas And Adenomas In Fap. (9th June 2014) - Mundre, P; Smith, L; Rehman, A; Rembacken, B
Abstract : Introduction: Although there is a low risk of malignant conversion of duodenal polyps in FAP, EMR is often considered. However, few studies have looked at the safety and efficacy of EMR. We compared the outcome of duodenal EMR's in patients with FAP vs sporadic adenomas. To our knowledge, this is the largest series of duodenal EMRs that is published so far. 1 Methods: We looked at Clinical records of all patients who underwent endoscopic resections for duodenal adenomas at Leeds in a 10 year period. Results: A total of 49 sporadic adenomas were resected (in 51 patients) and 44 FAP related (in 22 patients). Most lesions appeared either sessile (43) or flat elevated (48). The average size of the FAP related polyps was 16.9 vs. 20.7 mm in sporadic lesions. Most were removed by standard EMR (n = 82) rather than the strip biopsy technique (n = 9). Two procedures failed and no follow-up data was available after the resection of 2 sporadic polyps. The final histology of the lesions were; TA+LGD (76), TA+HGD (13), adenocarcinoma (2) and 2 polyps were not retrieved. In 11 lesions, there was a change in the histological grade after resection. There were 4 perforations (4.3%), 3 were managed surgically. 12 patients (13%) were readmitted with significant late GI bleeding and 8 patients required endoscopic therapy and transfusion. There was no significant difference in the success rates in the two groups (19/44 vs. 32/49) p value 0.94). However, the resection of polyps ≥2 cm were significantly more likely to be associated with a complication (7/59 vs. 8/19 p = 0.02). There was no difference in the risk of complications with the polyp location, ASA status, Spigelman score or patient age. Amongst the FAP polyps, polyps >20 mm were significantly more likely to have local recurrence (3/6 vs 3/31 p value 0.04). There was no difference in the chances of success of the resection with the growth pattern, the location of the polyp or the Spigelman score. Conclusion: Duodenal EMR is hazardous, particularly when lesions 2 cm or larger are resected. However, there was no significant difference in the hazards or success rates between the two groups. Most FAP patients had further neoplasia on follow up, but this is due to the fact that many of the adenomas were not resected /treated in the first sitting. Reference: 1 Basford P, Bhandari P. Endoscopic management of nonampullary duodenal polyps. Therap Adv Gastroenterol . 2012 March; 5(2):127–138 Disclosure of Interest: None Declared.